Equality in theory: From a heteronormative to an inclusive psychology of romantic love. (April 2019) - Thorne, Sapphira R.; Hegarty, Peter; Hepper, Erica G.
Since 1970, research on romantic relationships has burgeoned, but its theories and methods were shaped by a heteronormative cultural context. Heteronormativity is an ideology that implicitly holds that heterosexuality is, and should be, the only, dominant, or taken-for-granted sexuality for all. The movement towards sexual equality, particularly legal recognition of equal marriage, now allows psychologists to investigate romantic love in a more equal manner than ever before. To orient psychology towards less heteronormative theories of love, we make explicit how researchers in the past have (a) defined love and relationships as heterosexual, (b) presumed heterosexual patterns of love generalize to all, (c) used methodologies that introduce heterosexual bias, and (d) located differences in same-gender couples rather than between same-gender and opposite-gender couples. We conclude with recommendations on how critical thinking at all stages of research can make the difference between heteronormative and inclusive research on romantic love and relationships.